Comparative study of postoperative astigmatism in temporal scleral incision phacoemulsification versus temporal clear corneal incision phacoemulsification - Shivayogi R. Kusagur; B.H Manjunath; Poolan V. Nayak (Kerala Journal of Ophthalmology)
Context: Various modifications in cataract surgery have been tried to reduce postoperative astigmatism. Incision length and location are some variable modulations. In this view, we are comparing the astigmatism following scleral incision and clear corneal incision in phacoemulsification surgery with posterior chamber intra-ocular lens implantation. Aims: To compare postoperative astigmatism after temporal scleral incision phacoemulsification and temporal clear corneal incision phacoemulsification. Settings and Design: Nonrandomized Prospective Interventional Comparative hospital-based study. Methods and Materials: In 50 eyes, temporal scleral incision phacoemulsification is performed, and in 50 eyes, temporal clear corneal incision phacoemulsification is performed. The patients were examined on the 1st, 7th, and 30th postoperative days, and surgically induced astigmatism was calculated. Results: Mean surgically induced astigmatism in the temporal clear corneal incision phacoemulsification group Mean surgically induced astigmatism is 0.98 ± 0.39 on 1st postoperative day, 0.71 ± 26 after 1st postoperative week, and 0.68 ± 26 after postoperative 1 month. In the temporal scleral incision phacoemulsification group is 0.81 ± 0.24 on 1st postoperative day, 0.610 ± 0.16 after 1st postoperative week, and 0.55 ± 0.16 after postoperative 1 month. Conclusions: In this study, at any particular time temporal scleral incision group has less astigmatism compared to temporal clear corneal incision phacoemulsification group. Hence it can be stated that temporal scleral incision induces lesser astigmatism as compared to temporal clear corneal incision phacoemulsification.